Analisis Sosiologi Hukum atas Penyalahgunaan Wewenang Tindak Pidana Korupsi dalam perspektif Anomie dan Realisme Hukum - Gea, Muhammad Yasin Ali; Agusmidah, Agusmidah; Rosmalinda, Rosmalinda (Universitas Medan Area, 2025)
The abuse of authority in corruption cases in Indonesia can be more comprehensively examined through the lens of the sociology of law, particularly by applying Anomie Theory and Legal Realism. Corruption, as an extraordinary crime, persists despite the relative adequacy of the formal legal system (law in the books). This study employs a socio-legal method with a qualitative descriptive approach to explore the interplay between social structures and law enforcement practices in power-based corruption. The findings reveal that Anomie Theory explains corruption as a deviant “innovation” arising from the gap between cultural goals such as wealth and social status and the limited institutional means to achieve them lawfully. Conversely, Legal Realism emphasizes law in action, showing that judicial decisions and enforcement practices are often influenced by extra-legal factors such as political power, economic interests, and institutional pressure. This dynamic erodes the corrective function of formal law and undermines substantive justice. Although procedural justice may be achieved, public trust in the legal system continues to deteriorate, perpetuating a cycle of social anomie. The study concludes that effective anti-corruption efforts require not merely normative or positivist reforms, but also structural transformation in law enforcement and the reconstruction of social norms underpinning the moral legitimacy of law.